2015
DOI: 10.1016/j.chb.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding empathy training with virtual patients

Abstract: While the use of virtual characters in medical education is becoming more and more commonplace, an understanding of the role they can play in empathetic communication skills training is still lacking. This paper presents a study aimed at building this understanding by determining if students can respond to a virtual patient's statement of concern with an empathetic response. A user study was conducted at the [blinded] College of Medicine in which early stage medical students interacted with virtual patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
109
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 29 publications
0
109
1
Order By: Relevance
“…For example Kleinsmith et al (2015) has investigated empathy training with virtual patients. Here, though we consider only ethical problems in dealing with patients -where contrary to medical advice a patient demands a certain medicine; the first time that a doctor confronts this problem with a patient would typically be with a real patient.…”
Section: Doctor/patient Interactionmentioning
confidence: 99%
“…For example Kleinsmith et al (2015) has investigated empathy training with virtual patients. Here, though we consider only ethical problems in dealing with patients -where contrary to medical advice a patient demands a certain medicine; the first time that a doctor confronts this problem with a patient would typically be with a real patient.…”
Section: Doctor/patient Interactionmentioning
confidence: 99%
“…Virtual physiological humans can also be used to represent patients in the training of medical students, for example to detect cranial nerve abnormalities [2]. There is even an application for virtual avatars in training healthcare professionals to be more empathetic with promising initial results [3]. Medical students are asked to interview a virtual patient and the student's ability to respond empathetically at certain points in the interview can be evaluated in a systematic way.…”
Section: The Virtual Physiological Humanmentioning
confidence: 99%
“…For instance, early work by Johnsen et al (2007) showed a significant correlation between medical students' performance with a virtual and a human patient, and showed that medical students were able to elicit the same information from the real and virtual human (although showing less interest and poorer attitude toward the latter). More recently, virtual patients have been used in training for mental health assessment (Foster et al, 2015;Washburn et al, 2016), empathetic communication (Kleinsmith et al, 2015), and identifying gender bias in diagnosis (Rivera-gutierrez et al, 2014). In these studies, typically, human participants interacted with virtual patients via text or voice, and the virtual patients were animated and programmed to react toward the participants in a realistic way.…”
Section: Introductionmentioning
confidence: 99%